2014
DOI: 10.1002/2013jd021264
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of Arctic versus subarctic snow: Implications for high latitude passive microwave snow water equivalent retrievals

Abstract: Two unique observational data sets are used to evaluate the ability of multi-layer snow emission models to simulate passive microwave brightness temperatures (T B ) in high latitude, observation sparse, snow-covered environments. Data were utilized from a coordinated series of 18 sites measured across the subarctic Northwest Territories and Nunavut, Canada in April 2007 during a 1000 km segment of a 4200 km snowmobile traverse from Fairbanks, Alaska to Baker Lake, Nunavut (~64°N). In April 2011, a network of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 46 publications
(77 reference statements)
10
43
2
Order By: Relevance
“…Derksen et al, 2014;Essery and Pomeroy, 2004) than forested areas, whereas on the other hand, complicated canopy structure and small-scale ground topography affects the snow accumulation on the ground and increases the small-scale variability (e.g. Dobre et al, 2012;Storck et al, 2002); differences in snow depth and SWE variability (inter-quartile range in box plots in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Derksen et al, 2014;Essery and Pomeroy, 2004) than forested areas, whereas on the other hand, complicated canopy structure and small-scale ground topography affects the snow accumulation on the ground and increases the small-scale variability (e.g. Dobre et al, 2012;Storck et al, 2002); differences in snow depth and SWE variability (inter-quartile range in box plots in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…These winter melt-refreeze events modify the physical properties of snow (albedo, density, grain size, thermal conductivity), generate winter runoff (Bulygina et al, 2010; and can result in potentially significant impacts on the surface energy budget, hydrology and soil thermal regime (Boon et al, 2003;Hay and McCabe, 2010;Rennert et al, 2009). The refreezing of melt water can also create ice layers that adversely impact the ability of ungulate travel and foraging (Hansen et al, 2011;Grenfell and Putkonen, 2008), and exert uncertainties in snow mass retrieval from passive microwave satellite data (Derksen et al, 2014;Rees et al, 2010). Winter warming and melt events may also damage shrub species and tree roots, affecting plant phenology and reproduction in the Arctic (AMAP, 2011;Bokhorst et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to put these results into context, there are a number of studies that have quantified brightness temperature simulation errors for these models. These fall into different categories, depending on sensor characteristics, the source of the evaluation data (ground-based, airborne, satellite) and presence of ice lenses , the treatment of the snow microstructure (Picard et al, 2014), snow type, observation angle, and the specific electromagnetic model , and the underlying substrate (Lemmetyinen et al, 2009;Derksen et al, 2014). Examples of unscaled field observations of microstructure compared with ground-based observations include the HUT simulations of , who found an RMSE of 10-34 K, and Rutter et al (2014), who found a bias of 34-68 K that was reduced to < 0.6 K upon application of grain scale factors of 2.6-5.3.…”
Section: Discussionmentioning
confidence: 99%